Viperin Reveals Its True Function - Rivera-Serrano, Efraín E; Gizzi, Anthony S; Arnold, Jamie J; Grove, Tyler L; Almo, Steven C; Cameron, Craig E (Annual review of virology, 2020)
Most cells respond to viral infections by activating innate immune pathways that lead to the induction of antiviral restriction factors. One such factor, viperin, was discovered almost two decades ago based on its induction during viral infection. Since then, viperin has been shown to possess activity against numerous viruses via multiple proposed mechanisms. Most recently, however, viperin was demonstrated to catalyze the conversion of cytidine triphosphate (CTP) to 3'-deoxy-3',4'-didehydro-CTP (ddhCTP), a previously unknown ribonucleotide. Incorporation of ddhCTP causes premature termination of RNA synthesis by the RNA-dependent RNA polymerase of some viruses. To date, production of ddhCTP by viperin represents the only activity of viperin that links its enzymatic activity directly to an antiviral mechanism in human cells. This review examines the multiple antiviral mechanisms and biological functions attributed to viperin.